2016
DOI: 10.1016/j.jacc.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Gaps in Cardiovascular Care of the Older Adult Population

Abstract: The incidence and prevalence of most cardiovascular disorders increase with age, and cardiovascular disease is the leading cause of death and major disability in adults ≥75 years of age; however, despite the large impact of cardiovascular disease on quality of life, morbidity, and mortality in older adults, patients aged ≥75 years have been markedly underrepresented in most major cardiovascular trials, and virtually all trials have excluded older patients with complex comorbidities, significant physical or cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(65 citation statements)
references
References 88 publications
0
62
0
3
Order By: Relevance
“…There are critical knowledge gaps in the management of arrhythmias in the very elderly population, highlighted in a 2016 American College of Cardiology/American Heart Association/American Geriatrics Society scientific statement (109). We have summarized some important gaps in Table 4.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…There are critical knowledge gaps in the management of arrhythmias in the very elderly population, highlighted in a 2016 American College of Cardiology/American Heart Association/American Geriatrics Society scientific statement (109). We have summarized some important gaps in Table 4.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…Current evidence from trial data does not support a link between statins and cognitive dysfunction 7. However, concerns remain about the vulnerability of this age group to adverse effects from polypharmacy and the general lack of evidence to guide the prevention of CVD 8. A recent review of primary prevention studies of randomised controlled trials found no evidence of a reduction in CVD mortality in those older than 75, and it concluded that follow-up was too limited to exclude important adverse events from lipid lowering drugs 9.…”
Section: The Evidencementioning
confidence: 99%
“…Insights gained from this work should inform what may be the most important question, the true elephant in the room: why do people develop HFpEF in the first place? These inherently multidisciplinary efforts require “embracing [the] complexity” (57) of HFpEF, and incorporate many of the principles, assessment techniques, and translational research aims of geriatric cardiology (58,59). …”
Section: The Road Ahead In Hfpef: Embracing Complexitymentioning
confidence: 99%